The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/sd.1550
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable City: An Analytical–Deliberative Approach to Assess Policy in the Context of Sustainable Urban Development

Abstract: The Sustainable City study of the Netherlands Environmental Assessment Agency (PBL) uses an analytical-deliberative approach to generate integrated options for strategic, long-term urban development policies in the Netherlands. Scenarios for the sustainable city were designed using visions and roadmaps that were actively developed by actors involved in urban development and planning. The subsequent scenario analysis on potential, coherence and distributional effects across socio-economic groups was combined wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 11 publications
0
42
0
2
Order By: Relevance
“…This 'more urbanized less sustainable' pattern for Ability-1 of the spatial structure and function of the SMR is not surprising as cost effectiveness can hardly be ensured in urban spatial dynamics, especially in the use of transport energy (Black, 2009;Dassen et al, 2013;Firman, 2009). However, a similar pattern for Ability-3 can be seen as positive in rural areas, except those in Kabupatens Demak and Purwodadi, but negative for urban areas of the SMR.…”
Section: Resultsmentioning
confidence: 89%
“…This 'more urbanized less sustainable' pattern for Ability-1 of the spatial structure and function of the SMR is not surprising as cost effectiveness can hardly be ensured in urban spatial dynamics, especially in the use of transport energy (Black, 2009;Dassen et al, 2013;Firman, 2009). However, a similar pattern for Ability-3 can be seen as positive in rural areas, except those in Kabupatens Demak and Purwodadi, but negative for urban areas of the SMR.…”
Section: Resultsmentioning
confidence: 89%
“…Sustainable urbanization is an open and nonlinear complex system that encompasses society, economy, environment and other aspects [11,12] and its development process is a self-organizing system. Healthy and orderly urban development requires each element within the system to coordinate with and compete with each other, which was the driving force for the overall evolution of the sustainable urbanization system.…”
Section: Suss Analysismentioning
confidence: 99%
“…Sustainable urbanization requires that urban development satisfy the ecological, economic, and societal needs in an urban space [11,12] and also considers the demands of future generations; that is, sustainable urbanization is focused on the coordinated development of the population, the economy, urban spaces, the environment, and the overall society under geographical conditions (1) Analyses of the changes brought about by urbanization. Srinivasan et al [15] studied the relationship between urbanization and water resource vulnerability in a fast-growing city and found that some generalizable factors exist in the highly site-specific link between urbanization and water vulnerability, for which some feasible suggestions on water resource vulnerability were offered.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, many regions are now witnessing a steady process of industrialization and urbanization, leading to an significant volume of construction work performed in the developmental phases (Dassen et al, 2013). In order to enhance the sustainable development of the economics and society alongside environmental sustainability, it is crucial to establish an effective sustainability hierarchy addressing all of the triquetrous criteria of environmental, economic, and social aspects (Manan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%